KAJIAN PSIKOLOGI SASTRA DALAM CERPEN “PEREMPUAN BALIAN” KARYA SANDI FIRLI - Setiaji, Aria Bayu (LP2M IAIN Ambon, 2019)
Abstract This study aims to describe: (1) structural aspects of Balian Women's Short Story by Sandi Firly (2) psychological aspects of Balian Women's Short Story. This type of research is qualitative research. The data source of this research is the Short Story of Balian Woman by Sandi Firly published by Kompas on June 24, 2012. The data of this research are sentences containing structural and psychological elements. Data collection techniques used were document techniques, refer to techniques and note taking techniques. The technique used to present the results of data analysis in this study is the informal presentation technique. The results of this study indicate that: 1) the structural aspects of Balian Women's Short Stories by Sandi Firly include; (a) characterizations using analytic and dramatic techniques, (b) plot in the story using conventional plot, (c) the setting in this short story covers, background (meratus mountains, Balai atiran, small village, small shop and forest of South Kalimantan), background the time at night and the days after the event at night, and the social setting still believes in superstition. (d) Persona I's first perspective (2) The psychological aspect of the personality structure of the character in the short story of Balian Woman by Sandi Firly has three elements, namely id, ego, and superego. The three elements of the personality structure influence the behavior, mindset, and mentality of the main characters in the short story of the Woman Balian. From the psychological analysis above, it can be seen that the characters have a strong id. They tend to want to break away from all the problems they feel in life without seeing the reality that exists. Keywords: Psychology, Short Stories Abstrak Penelitian ini bertujuan mendeskripsikan: (1) aspek struktural Cerpen Perempuan Balian karya Sandi Firly (2) aspek psikologis Cerpen Perempuan Balian.Jenis penelitian ini adalah penelitian kualitatif. Sumber data penelitian ini adalah Cerpen Perempuan Balian karya Sandi Firly diterbitkan oleh Kompas pada 24 Juni 2012. Data penelitian ini berupa kalimat yang mengandung unsur struktural dan psikologi. Teknik pengumpulan data yang digunakan adalah teknik dokumen, teknik simak dan teknik catat. Dalam penelitian ini, peneliti menggunakan teknik analisis isi sebagai teknik analisis data. Teknik yang digunakan untuk menyajikan hasil analisis data dalam penelitian ini adalah teknik penyajian informal. Hasil penelitian ini menunjukkan bahwa: 1) aspek struktural pada Cerpen melipui; (a) penokohan menggunakan teknik analitik dan teknik dramatic, (b) Alur dalam cerita mengunakan alur konvensional, (c) latar pada cerpen ini meliputi, latar tempat (pegunungan meratus, Balai atiran, kampong kecil, warung dan hutan Kalimantan selatan) , latar waktu pada malam hari dan hari-hari setelah peritiwa pada malam, dan latar sosial masih percaya dengan tahayul. (d) sudut pandang Persona pertama Aku (2) Aspek psikologi struktur kepribadian tokoh dalam cerpen Perempuan Balian karya Sandi Firly memiliki tiga unsur, yaitu id, ego, dan superego. Ketiga struktur kepribadian tersebut memengaruhi tingkah laku, pola pikir, dan kejiwaan para tokoh utama dalam cerpen Perempuan Balian . Dari analisis psikologi di atas, diketahui bahwa para tokoh memiliki id yang kuat. Mereka cenderung ingin melepaskan diri dari segala permasalahannya dalam hidup tanpa melihat realita yang ada. Kata Kunci : Psikologi, Cerpen